Academic writing as love. Issue 3 (July 2018) - Kiriakos, Carol Marie; Tienari, Janne
Writing is presented in hegemonic academic discourse as a rational and predictable activity that targets publications in the right journals. Nevertheless, many academics struggle with writing. In this article, we draw attention to how writing is experienced as an embodied, sensuous, emotional, social, and identity-related activity. Specifically, we aim to advance this comprehensive understanding of academic writing with the concept of love. By understanding love as action rather than feeling, we can foster our love for writing both as practice and in practice. We can learn to deal with the struggle by writing every day and approaching writing with dedication. By advocating the perspective of love, we seek to encourage discussion on academic writing so that it reflects the multifaceted experiences of writers, and unleash its potential in confusing and disrupting the masculine order in academia. Love offers a language to talk about vulnerability and courage, and viewing writing in the light of love helps us to learn more about ourselves and our activities as writers of management.